Local Wisdom of the Paser Community in the New Capital City Nusantara (IKN) as an Alternative to Traditional Community Conflict Resolution : Kearifan Lokal Masyarakat Paser di Wilayah Ibu kota Nusantara (IKN) Sebagai Alternatif Resolusi Konflik Tradisional Masyarakat - Norhidayat; Rey Samuel; Muhammad Rangga; Hendi Sopian; Mbara, Herlina; Desti Eka Sari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Indonesia is a country rich in culture and local wisdom of its people, it is not surprising because Indonesia is blessed with many tribes and ethnic communities. This diversity makes Indonesia more colorful and remains intact under the guise of Bhinneka Tunggal Ika. One of the unique cultures in the Indonesian capital region is the local wisdom of the Paser people, namely Mayar Sala. This tradition is part of the community's traditional conflict resolution ceremonies and has been carried out for generations. This research is a qualitative research method that describes the local wisdom of Mayar Sala and its contribution to conflict resolution in the IKN area. Data collected through in-depth interviews with the community and traditional actor as well as collection from written sources from articles, books and archives in the regional library of East Kalimantan Province. During the research process, researchers discovered many new things, such as the meaning of Mayar Sala, which means paying wrongly. Furthermore, researchers also discovered how this tradition began to exist as well as the types of Mayar Sala ceremony traditions. Researchers also discovered the inheritance from generation to generation of this tradition and its contribution to maintaining peace in the East Kalimantan region so that ideally the region was chosen as part of the new National Capital (IKN) because of the lack of conflict in the region.